2020
DOI: 10.4322/acr.2020.202
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of radiation-induced brachial plexopathy with omentoplasty

Abstract: Radiation-induced brachial plexus neuropathy (RIBPN) is a rare and delayed non-traumatic injury to the brachial plexus, which occurs following radiation therapy to the chest wall, neck, and/or axilla in previously treated patients with cancer. The incidence of RIBPN is more common in patients treated for carcinoma of the breast and Hodgkin lymphoma. With the improvement in radiation techniques, the incidence of injury to the brachial plexus following radiotherapy has dramatically reduced. The currently reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…In fact, the U.S. death rate from breast cancer declined by 40% between 1989 and 2017, 36 thus supporting increased longevity from the disease with a greater opportunity for developing very late effects of treatment. Recently published case reports support the finding that very late effects of radiation therapy (after 15–20 years) continue to result in RIBP in survivors of breast cancer, 18,37–39 as well as in a patient with nasopharyngeal cancer 5 . As Bajrovic et al 40 noted in their study of RIBP after supraclavicular lymph node radiotherapy: “a follow‐up period of 5 years … is too short a time a time interval for recording the majority of lesions occurring in total.”…”
Section: Literature Reviewmentioning
confidence: 83%
“…In fact, the U.S. death rate from breast cancer declined by 40% between 1989 and 2017, 36 thus supporting increased longevity from the disease with a greater opportunity for developing very late effects of treatment. Recently published case reports support the finding that very late effects of radiation therapy (after 15–20 years) continue to result in RIBP in survivors of breast cancer, 18,37–39 as well as in a patient with nasopharyngeal cancer 5 . As Bajrovic et al 40 noted in their study of RIBP after supraclavicular lymph node radiotherapy: “a follow‐up period of 5 years … is too short a time a time interval for recording the majority of lesions occurring in total.”…”
Section: Literature Reviewmentioning
confidence: 83%
“…Microvascular omental flap had been reported to treat RIBP to improve neuropathic pain. 12,13 We used pedicled muscular flap to improve the soft conditions around the brachial plexus. The pedicled muscular flap was used in 6 cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Microvascular omental flaps, pulsed radiofrequency ablation, and hyperbaric oxygen therapy had been reported to treat RIBP with painful palsies. [11][12][13][14] There were few reports of treatment, which could improve the movement function of the patients suffered from RIBP. In the management of RIBP, it is a challenge to attain useful motor function.…”
mentioning
confidence: 99%
“…Treatments to address pain include oral neuropathic pain medications (tricyclic antidepressants, selective serotonin-norepinephrine inhibitors, gabapentin), steroids, and pulsed radiofrequency ablation. 47,48 A study of hyperbaric oxygen for 34 patients with radiation-induced brachial plexopathy found no benefit to motor function, but 2 patients had improvement in temperature sensation. 49 A 1994 study demonstrated recovery of function in two patients with radiation plexopathy after anticoagulation for 3 to 6 months, but there have no further studies of this treatment.…”
Section: Radiation-related Nerve Injurymentioning
confidence: 99%
“…Nerve conduction studies demonstrate both direct axonal injury and demyelination. 44 The pathophysiology of delayed radiation-induced nerve injury is favored to be perineural fibrosis with the resulting obstruction of small arterioles which results in ischemia to the capillary networks supplying the nerves 45,47 and the production of neo-vascularization, which is thought to be irreversible.…”
Section: Radiation-related Nerve Injurymentioning
confidence: 99%